Designing food experiences for well-being: a framework advancing design thinking research from a customer experience perspective. (27th May 2021) - Batat, Wided; Addis, Michela
Abstract : Purpose: Literature from across design studies and innovation management, as well as food marketing research evidence, is examined to highlight the interdisciplinary and experiential research approaches to food consumption and well-being. This conceptual paper aims to address the need to expand the food industry's goals by considering its contributions to the consumer's overall food well-being. Food experience design (FED) seeks to understand how food professionals can design healthy and pleasurable food experiences aimed at enhancing people's food well-being. FED does so by proposing a holistic and integrative framework. Design/methodology/approach: This approach examines design thinking by conducting an analysis of the multidisciplinary literature. This paper addresses the gap in the literature by advancing the theoretical and empirical understanding of food design thinking through the lenses of experiential theory and consumer well-being. Findings: This review paper clarifies the scope of FED scholarship and offers a call for collective efforts to establish a focused body of knowledge that leads food marketing professionals and scholars to adopt an experiential perspective to food consumption and production focused on experiential pleasure of food as a driving force for consumer's well-being. Research limitations/implications: The review paper addresses the need to expand the food industry's goals by considering its contributions to the consumer's overall food well-being. FED seeks to understand how food professionals can design healthy and pleasurable food experiences aimed at enhancing people's food well-being. FED does so by proposing a holistic and integrative framework. Practical implications: This research provides designers with the operative tools to create innovative food experiences and increase the food well-being of consumers. Toward that end, designers need to extend their skills and evolve their language and competencies to create valuable dialogues with other stakeholders involved. Collaboration requires many other premises. This paper contributes to the discussion by identifying and clarifying them. Originality/value: This research highlights the imperative to take multidisciplinary, transformative and experiential approaches to researching food innovation strategies from a consumer's well-being perspective.